ANALISA KETERPADUAN PASAR KOPI DAN KARET INDONESIA - Sukiyono, Ketut; Sriyoto, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
Processing coffe industry at Bengkulu city face with finacial, production technology and market information burdens,generally. Its later affect to the industrys’ competitive advantage Commonly, the compettitve advantage was good, its showed by revenue-cost ratio about 1,26.